2007
DOI: 10.1107/s1600536807028899
|View full text |Cite
|
Sign up to set email alerts
|

The Heusler-type alloy MgZn2Ce

Abstract: Key indicators: single-crystal X-ray study; T = 295 K; mean (Ce-Mg) = 0.002 Å; R factor = 0.016; wR factor = 0.045; data-to-parameter ratio = 11.0.Single crystals of the MgZn 2 Ce alloy (magnesium dizinc cerium) were synthesized by a two-step method which couples the thermal treatment of pressed pellets of the pure elements with subsequent arc melting. The compound crystallizes in a Heusler-type (MnCu 2 Al) structure in the space group Fm3m, with one Zn site (site symmetry 43m), one Ce and one Mg site (both wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The last compound was found to crystallize with a cubic unit cell (a ¼ 7064 Å) whereas the crystal structures of the other above mentioned compounds remained unknown. In our previous works we reported about the crystal structures of cubic CeMgZn 2 (Fm-3m, a ¼ 7.0358(4) Å) [4], Ce 20 Mg 19 Zn 81 (F-43m, a ¼ 21.1979(8) Å) [5] and orthorhombic Ce 3 (Zn 0.863 Mg 0.137 ) 11 [6] ternary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The last compound was found to crystallize with a cubic unit cell (a ¼ 7064 Å) whereas the crystal structures of the other above mentioned compounds remained unknown. In our previous works we reported about the crystal structures of cubic CeMgZn 2 (Fm-3m, a ¼ 7.0358(4) Å) [4], Ce 20 Mg 19 Zn 81 (F-43m, a ¼ 21.1979(8) Å) [5] and orthorhombic Ce 3 (Zn 0.863 Mg 0.137 ) 11 [6] ternary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The decagonal quasicrystal reported in many of the Mg-Zn-RE systems was not observed in the Mg-Zn-Ce system [13]. Pavlyuk et al reported a Heusler-type alloy with the composition CeMgZn 2 [14] and a cubic phase Ce 20 Mg 19 Zn 81 [15]. Crystallographic data and compositions of all ternary phases accepted in the present study are summarized in Table 1.…”
Section: Experimental Data In the Literaturementioning
confidence: 79%
“…They examined the solid solubilities of binary and ternary solutions by EDS and EPMA. In addition to the four ternary phases reported previously [6], two new ternary phases, Ce 2 Mg 53 Zn 45 and Ce 6 Mg (8)(9)(10)(11)(12)(13)(14)(15) Zn , were found in their work. The decagonal quasicrystal reported in many of the Mg-Zn-RE systems was not observed in the Mg-Zn-Ce system [13].…”
Section: Experimental Data In the Literaturementioning
confidence: 80%
See 2 more Smart Citations